2022
DOI: 10.1038/s41598-021-04409-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of composite electrodes based on rGO, Mn/Cu metal–organic frameworks, and PANI

Abstract: Benzendicarboxylic acid (BDC)-based metal–organic frameworks (MOFs) have been widely utilized in various applications, including supercapacitor electrode materials. Manganese and copper have solid diamond frames formed with BDC linkers among transition metals chosen for MOF formation. They have shown the possibility to enlarge capacitance at different combinations of MOFs and polyaniline (PANI). Herein, reduced graphene oxide (rGO) was used as the matrix to fabricate electrochemical double-layer SCs. PANI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…33 Compositing with other materials such as carbon based materials (carbon nanotubes and graphene), inorganic oxides (such as SnO 2 , MnO 2 , TiO 2 ), sulphides and hydroxides and other metal compounds have been proved to enhance cyclic stability as well as maximize the capacitance of resultant composites. 6,15,33,[36][37][38][39][40][41][42] In order to alleviate the limitation associated with PANImatrix for charge storage application, PANI was added inside synthesized mesoporous silicon (which contains mixed pores within mesoporosity range) to increase its charge storage, cyclic stability and specic capacitance. Besides this, PANI was also added in the mesoporous silica under same conditions and was compared with simple PANI and PANI with mesoporous silicon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Compositing with other materials such as carbon based materials (carbon nanotubes and graphene), inorganic oxides (such as SnO 2 , MnO 2 , TiO 2 ), sulphides and hydroxides and other metal compounds have been proved to enhance cyclic stability as well as maximize the capacitance of resultant composites. 6,15,33,[36][37][38][39][40][41][42] In order to alleviate the limitation associated with PANImatrix for charge storage application, PANI was added inside synthesized mesoporous silicon (which contains mixed pores within mesoporosity range) to increase its charge storage, cyclic stability and specic capacitance. Besides this, PANI was also added in the mesoporous silica under same conditions and was compared with simple PANI and PANI with mesoporous silicon.…”
Section: Introductionmentioning
confidence: 99%
“…33 Compositing with other materials such as carbon based materials (carbon nanotubes and graphene), inorganic oxides (such as SnO 2 , MnO 2 , TiO 2 ), sulphides and hydroxides and other metal compounds have been proved to enhance cyclic stability as well as maximize the capacitance of resultant composites. 6,15,33,36–42…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that using CNT@MOF core-shell structures as an electrode resulted in a high initial capacitance of 150.7 F g −1 at 0.1 A g −1 in 1 M Na 2 -SO 4 solution and good capacity retention of 83.5% after 10 000 cycles at 4 A g −1 . A reduced graphene oxide (rGO) was used as the matrix to fabricate electrochemical double-layer supercapacitors (SCs) by Le et al 223 PANI and Mn/Cu-MOF's effect on the properties of electrode materials was investigated through electrochemical analysis and the highest specific capacitance of about 276 F g −1 at a current density of 0.5 A/g was obtained for the rGO/Cu-MOF@PANI composite (see Fig. 10).…”
Section: Electrochemical Charge Storagementioning
confidence: 99%
“…Under these circumstances, the BTC-900//AC ASC device reaches a maximum energy density of 24.02 W h kg −1 at a power density of 825 W kg −1 , which is comparable to recently reported peer references. [55][56][57][58] The detailed energypower density value is listed in Fig. 4a.…”
Section: Papermentioning
confidence: 99%